Surgical site infections prevalence among caesarean section patients - Tasneem Alkout; Abdulhamid M. Alkout; Esraa Rasheed; Osama Etekbali; Fathi Abousnina; Alhadi Araibi (Iberoamerican Journal of Medicine)
Introduction: Cesarean section is one of the most prevalent surgical procedures in the world and Surgical Site Infections (SSI) are the most common complication following Cesarean section. This leads to greater patient dissatisfaction, longer hospital stays, and higher treatment costs. The aim of this retrospective study is to determine the prevalence of wound infection and the prevalence of bacterial isolates in post-Cesarean section and its sensitivity to variant antibiotics. Material and methods: Samples were collected from patients who had developed wound infection following cesarean section and cultured on blood, chocolate and chromatic agar. The isolated bacteria was identified by ordinary microbiology techniques. Results: Among 4,482 Cesarean section patients in Albaraa Hospital, the surgical site infections (SSI) rate was 2.94 %. Microorganisms isolated from these cases included Candida albicans at a rate of 0.11%. The remaining 2.83% were bacterial isolates, with 70.1% being gram-positive bacteria significantly higher than the 29.9% attributed to gram-negative bacteria (P = 0.01). The main bacteria isolates were Staphylococcus aureus (37.8%), Staphylococcus epidermidis (23.6%), Pseudomonas aeruginosa (11.4%), Klebsiella pneumonia (8.3%), Escherichia coli (5.3%) and Alpha hemolytic Streptococcus (3.8%) Conclusions: The SSI rate in this study was at the lower limit of the WHO predicted infection rate and the bacterial isolates were sensitive to many antibiotics. This result may be due to the pre, intra and postoperative prophylactic antibiotics administered to patients and other factors such as short hospital stay and staff training in aseptic techniques. This study recommends further assessment of SSI in alternative surgical procedures, and assess the efficiency of prophylactic antibiotics in alternative surgeries in Libya.